Hubungan hipertensi dengan stroke pada pasien Poliklinik Neurologi RSUP Sanglah Denpasar - I Made Fermi Wikananda; Ida Bagus Kusuma Putra; I Wayan Widiantara (DiscoverSys Inc., 2019)
Introduction: Stroke is a disease which has a fairly high morbidity and mortality caused by the cessation of blood supply to the brain. The most common risk factor for stroke is high blood pressure or hypertension. In patients with hypertension, blood vessel damage can be occured which triggers thrombosis and atherosclerosis, leads to non hemorrhagic stroke and also weak and thin blood vessels with aneurysms can be found that induce hemorrhagic stroke. This study aimed to determine the relationship of hypertension and stroke in patients at the Neurology Clinic in Sanglah General Hospital, DenpasarMethod: This study was a cross-sectional study involving 100 patients. Secondary data were taken from the medical records of hypertensive and/or stroke patients in the Neurology Clinic of Sanglah General Hospital, Denpasar, from January 1, 2017 to December 31, 2018.Result: The results of bivariate analysis showed a strong and significant relationship between hypertension and stroke (PR = 2.37; 95% CI PR: 1.03 â€“ 8.21; p = 0.04). There was a significant relationship between hypertension and stroke after being controlled by confounding variables (Î² = 1,267; odds ratio = 3,549; 95% CI: 10,801 - 1,166; p = 0,026). Diabetes mellitus, dyslipidemia, arrhythmia, smoking, obesity did not have a significant relationship with stroke.Conclusion: There was a significant relationship between hypertension and stroke in patients at the Neurology Clinic in Sanglah General Hospital, Denpasar.Â Latar Belakang: Stroke adalah sebuah penyakit yang memiliki morbiditas dan mortalitas cukup tinggi yang diakibatkan oleh terhentinya suplai darah ke otak. Faktor resiko dari stroke yang paling sering dijumpai adalah tekanan darah tinggi atau hipertensi. Pada pasien dengan hipertensi dapat terjadi kerusakan pembuluh darah yang memicu adanya trombosis dan aterosklerosis yang memicu stroke penyumbatan dan ditemukan pula pembuluh darah yang menjadi lemah dan menipis disertai aneurisma yang memicu stroke pendarahan. Penelitian ini bertujuan untuk mengetahui hubungan hipertensi dengan stroke pada pasien di Poliklinik Neurologi RSUP Sanglah Denpasar.Metode: Penelitian ini merupakan studi potong lintang dengan melibatkan sampel sebanyak 100 orang. Data sekunder diambil dari rekam medis pasien hipertensi dan/atau stroke di Poliklinik Neurologi RSUP Sanglah Denpasar periode 1 Januari 2017 sampai 31 Desember 2018.Hasil: Hasil analisis bivariat menunjukkan hubungan yang kuat dan bermakna antara hipertensi dan stroke (RP = 2,37; IK 95% RP: 1,03 â€“ 8,21; p = 0,04). Hubungan antara hipertensi dengan stroke setelah dikontrol dengan variable-variabel perancu didapatkan hubungan yang signifikan (Î² = 1,267; odds ratio = 3,549; IK 95%: 10,801 - 1,166; p = 0,026). Diabetes melitus, dislipidemia, aritmia, merokok, obesitas tidak memiliki hubungan yang bermakna dengan stroke.Simpulan: Terdapat hubungan yang bermakna antara hipertensi dengan stroke pada pasien yang datang ke Poliklinik Neurologi RSUP Sanglah Denpasar.